Investigating the Role of Social Functions of Parks on Adherence to Physical Activity of Elderly People During an Epidemic Disease (COVID-19) - Azimkhani, Amin; Honari, Habib; Türkmen, Mutlu; Gholamian, Javad; Saatchian, Vahid; Salari, Reyhane (Progress in Nutrition, 2021)
Introduction: The importance of desirable physical activity as a deterrent and risk factor for the elderly is well known. The present study was conducted to investigate the role of parks’ social functions on adherence to physical activity in elderly people in Mashhad During epidemic disease (COVID-19). Method: This cross-sectional study was performed using a structured interview technique and a multi-part questionnaire on 100 elderly people. Sampling was done in two stages using a systematic random method. Results: Based on the results, it was found that there is a positive and significant relationship between the social function of parks and its components with adherence to physical activity in the elderly (P <0.05) and well as 18% of adherence to physical activity changes is related to the social function of parks. Conclusion: The findings of this study showed that many factors are affecting physical activity in elderly people, which understanding these factors help educators and other health professionals in designing appropriate intervention programs. Maintaining regular PA during self-isolation is important for the prevention of future chronic health conditions due to a sedentary lifestyle. During crises, functional medical care and vital societal services are of the highest priority.